Patterns of differences in wayfinding performance and correlations among abilities between persons with and without Down syndrome and typically developing children - Davis, Megan; Merrill, Edward C.; Conners, Frances A.; Roskos, Beverly (Frontiers in Psychology, 2014)
Two experiments are reported that evaluated route learning of youth with DS, youth with Intellectual Disability and not DS (ID), and typically developing children (TD) matched on Mental Age (MA). In both experiments, participants learned routes with eight choice-points presented via computer. Several objects were placed along the route that could be used as landmarks. Participants were shown the correct route once and then were asked retraced the route without assistance. In Experiment 1 we found that the TD children and ID participants performed very similarly. They learned the route in the same number of attempts, committed the same number of errors while learning the route, and recalled approximately the same number of landmarks. The participants with DS performed significantly worse on both measures of navigation (attempts and errors) and also recalled significantly fewer landmarks. In Experiment 2, we attempted to reduce TD and ID vs DS differences by focusing participants’ attention on the landmarks. Half of the participants in each group were instructed to identify the landmarks as they passed them the first time. The participants with DS again committed more errors than the participants in the ID and TD groups in the navigation task. In addition, they recalled fewer landmarks. While landmark identification improved landmark memory for both groups, it did not have a significant impact on navigation. Participants with DS still performed more poorly than did the TD and ID participants. Of additional interest, we observed that the performance of persons with DS correlated with different ability measures than did the performance of the other groups. The results the two experiments point to a problem in navigation for persons with DS that exceeds expectations based solely on intellectual level.